LOYALITAS NASABAH PADA PT BANK YUDHA BHAKTI TBK - Lugas Handrogumarang (2017)
Bank is a company engaged in the services sector. Range of products offered by banks, such as savings and loan product. Savings and loan products is an excellent product that is offered in the banking industry. This study was conducted to see wether or not the influence of customer relationship marketing to the growing sense of loyalty through trust. Customer relationship marketing is influenced by the commitment, communication, and handling of complaints. Confidence is affected by concern for the security of transactions, consistency in quality service delivery, and the respect shown by the bank employees. Loyalty can be detected by the repeat purchase behavior, still choose the company, recommending the company, and have confidence that the brand is best. Data collection techniques using primary data by spreading questionnaires to 50 respondents. The sampling technique in this research is Non-Probability Sampling with Purposive Sampling method. Mechanical analysis using Partial Least Square (PLS ). The results stated customer relationship marketing direct significant effect on customer loyalty. In this study it can be stated that customer relationship marketing indirectly significant effect on customer loyalty through customer confidence.